Angiotensin‐(1‐7)/Mas receptor agonist: a disease modifying therapeutic for VCID protects cognitive function and inhibits serum neurofilament light protein. (20th December 2022) - Hoyer‐Kimura, Christina; Konhilas, John; Sweitzer, Nancy; Ryan, Lee; Hay, Meredith
Abstract: Background: Vascular contributions to cognitive impairment and dementia (VCID) and Alzheimer's disease related dementias (ADRD) are associated with increases in systemic and brain inflammatory cytokines, increased reactive oxygen species (ROS) and decreased brain blood flow. We have completed preclinical development of novel synthetic glycopeptide derivatives of Angiotensin‐(1‐7) (Ang‐1‐7) MasR agonists that have outstanding brain penetration, improved half‐life, reverse cognitive impairment and decreases plasma neurofilament light protein (NfL) in our preclinical model of VCID. Ang‐(1‐7)/MasR mechanisms of action include inhibition of 1) microglia activation, 2) brain cytokines activation and, 3) vascular endothelial ROS production. The purpose of this pilot study was to 1) determine if plasma NfL is increased in coronary artery bypass graft (CABG) surgery patients at‐risk for VCID and 2) determine if treatment with an Ang‐(1‐7)/MasR agonist protects cognitive function post‐surgy and modifies NfL. Method: Subjects were randomly assigned to receive either 200 micrograms/kg/day s.c. (n = 3) or saline‐placebo (n = 2). Injections were begun 2 hours prior to surgery and then daily for 21 days. Cognitive function was measured prior to surgery and at 21‐ and 90‐days post‐surgery. Serum NfL was measured via Quanterix Simoa assay. Statistical analysis was performed using GraphPad and significance tested using Welch's ANOVA, Dunnett's post. Memory function was measured using a composite score comprised of memory, executive functioning, language, and processing speed. Result: Plasma levels of NfL prior to surgery were significantly increased by 176% in CABG patients (n = 5) as compared to age‐matched healthy controls (n = 8, p = .003). Treatment with Ang‐(1‐7) for 21‐days via subcutaneous injections protected memory function as measured by both the Face‐Name and Cured Name Retrieval associative memory tests at both 21‐ and 90‐days post ‐surgery and significantly attenuated CABG induced increases in NfL as compared to placebo‐saline treatment (p = .004). Conclusion: These preliminary data suggest that NfL may serve as a biomarker of VCID in CABG surgery patients and for MasR target engagement for VCID‐modifying treatments with Ang‐(1‐7) analogs. We have begun studies to develop NfL as a biomarker for Ang‐(1‐7)/MasR target activation and for patient stratification for treatment of VCID (Supported by NIH U01HL131014, U01AG066623).